Development of a battery management system interface for adapting second life batteries to energy storage - Jorge Lopes dos Santos Teixeira Carrondo (2019)
As technology progresses so does the need to adapt and repurpose components and practices that need to be improved for the sake of efficiency, environmental protection, financial sustainability and, overall, to obtain the best final product. With the advent of electric vehicles, surges the issue of the used batteries for vehicles, namely cars such as Tesla (Models X and S), VW (GTE, E-Golf and E-Up), Nissan (Leaf and NV200) and BMW i3. After its normal daily use the battery might not be suited anymore to be used again in a different vehicle since it requires Power, however, there is still an important and ever growing use case for said battery as an energy storage unit for domestic and industrial installations paired up with renewable energy injection. In order to safely and accurately provide energy there is a need of technical and theoretical expertise not only for installing the system but to regulate it too.